394 lines
14 KiB
Text
394 lines
14 KiB
Text
----------------------------------------------------------------------------------------------------
|
||
--- Copyright (c) 2014 Parikshit Khanna. All rights reserved.
|
||
--- Released under Apache 2.0 license as described in the file LICENSE.
|
||
--- Authors: Parikshit Khanna, Jeremy Avigad
|
||
----------------------------------------------------------------------------------------------------
|
||
|
||
-- Theory list
|
||
-- ===========
|
||
--
|
||
-- Basic properties of lists.
|
||
|
||
import tactic
|
||
import nat
|
||
|
||
using nat
|
||
using eq_proofs
|
||
|
||
namespace list
|
||
|
||
|
||
-- Type
|
||
-- ----
|
||
|
||
inductive list (T : Type) : Type :=
|
||
| nil {} : list T
|
||
| cons : T → list T → list T
|
||
|
||
infix `::` : 65 := cons
|
||
|
||
section
|
||
|
||
variable {T : Type}
|
||
|
||
theorem list_induction_on {P : list T → Prop} (l : list T) (Hnil : P nil)
|
||
(Hind : forall x : T, forall l : list T, forall H : P l, P (cons x l)) : P l :=
|
||
list_rec Hnil Hind l
|
||
|
||
theorem list_cases_on {P : list T → Prop} (l : list T) (Hnil : P nil)
|
||
(Hcons : forall x : T, forall l : list T, P (cons x l)) : P l :=
|
||
list_induction_on l Hnil (take x l IH, Hcons x l)
|
||
|
||
notation `[` l:(foldr `,` (h t, cons h t) nil) `]` := l
|
||
notation `[` `]` := nil
|
||
-- TODO: should this be needed?
|
||
notation `[` x `]` := cons x nil
|
||
|
||
|
||
-- Concat
|
||
-- ------
|
||
|
||
definition concat (s t : list T) : list T :=
|
||
list_rec t (fun x : T, fun l : list T, fun u : list T, cons x u) s
|
||
|
||
infixl `++` : 65 := concat
|
||
|
||
theorem nil_concat (t : list T) : nil ++ t = t := refl _
|
||
|
||
theorem cons_concat (x : T) (s t : list T) : (x :: s) ++ t = x :: (s ++ t) := refl _
|
||
|
||
theorem concat_nil (t : list T) : t ++ nil = t :=
|
||
list_induction_on t (refl _)
|
||
(take (x : T) (l : list T) (H : concat l nil = l),
|
||
show concat (cons x l) nil = cons x l, from H ▸ refl _)
|
||
|
||
-- TODO: these work:
|
||
-- calc
|
||
-- concat (cons x l) nil = cons x (concat l nil) : refl (concat (cons x l) nil)
|
||
-- ... = cons x l : {H})
|
||
|
||
-- H ▸ (refl (cons x (concat l nil))))
|
||
|
||
-- doesn't work:
|
||
-- H ▸ (refl (concat (cons x l) nil)))
|
||
|
||
theorem concat_assoc (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) :=
|
||
list_induction_on s (refl _)
|
||
(take x l,
|
||
assume H : concat (concat l t) u = concat l (concat t u),
|
||
calc
|
||
concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _
|
||
... = cons x (concat l (concat t u)) : { H }
|
||
... = concat (cons x l) (concat t u) : refl _)
|
||
|
||
-- TODO: deleting refl doesn't work, nor does
|
||
-- H ▸ refl _)
|
||
|
||
-- concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _
|
||
-- ... = concat (cons x l) (concat t u) : { H })
|
||
|
||
-- concat (concat (cons x l) t) u = cons x (concat l (concat t u)) : { H }
|
||
-- ... = concat (cons x l) (concat t u) : refl _)
|
||
|
||
-- concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _
|
||
-- ... = cons x (concat l (concat t u)) : { H }
|
||
-- ... = concat (cons x l) (concat t u) : refl _)
|
||
|
||
-- add_rewrite nil_concat cons_concat concat_nil concat_assoc
|
||
|
||
|
||
-- Length
|
||
-- ------
|
||
|
||
definition length : list T → ℕ := list_rec 0 (fun x l m, succ m)
|
||
|
||
-- TODO: cannot replace zero by 0
|
||
theorem length_nil : length (@nil T) = zero := refl _
|
||
|
||
theorem length_cons (x : T) (t : list T) : length (x :: t) = succ (length t) := refl _
|
||
|
||
theorem length_concat (s t : list T) : length (s ++ t) = length s + length t :=
|
||
list_induction_on s
|
||
(calc
|
||
length (concat nil t) = length t : refl _
|
||
... = zero + length t : {symm (add_zero_left (length t))}
|
||
... = length (@nil T) + length t : refl _)
|
||
(take x s,
|
||
assume H : length (concat s t) = length s + length t,
|
||
calc
|
||
length (concat (cons x s) t ) = succ (length (concat s t)) : refl _
|
||
... = succ (length s + length t) : { H }
|
||
... = succ (length s) + length t : {symm (add_succ_left _ _)}
|
||
... = length (cons x s) + length t : refl _)
|
||
|
||
-- -- add_rewrite length_nil length_cons
|
||
|
||
|
||
-- Reverse
|
||
-- -------
|
||
|
||
definition reverse : list T → list T := list_rec nil (fun x l r, r ++ [x])
|
||
|
||
theorem reverse_nil : reverse (@nil T) = nil := refl _
|
||
|
||
theorem reverse_cons (x : T) (l : list T) : reverse (x :: l) = (reverse l) ++ (cons x nil) := refl _
|
||
|
||
-- opaque_hint (hiding reverse)
|
||
|
||
theorem reverse_concat (s t : list T) : reverse (s ++ t) = (reverse t) ++ (reverse s) :=
|
||
list_induction_on s
|
||
(calc
|
||
reverse (concat nil t) = reverse t : { nil_concat _ }
|
||
... = concat (reverse t) nil : symm (concat_nil _)
|
||
... = concat (reverse t) (reverse nil) : {symm (reverse_nil)})
|
||
(take x l,
|
||
assume H : reverse (concat l t) = concat (reverse t) (reverse l),
|
||
calc
|
||
reverse (concat (cons x l) t) = concat (reverse (concat l t)) (cons x nil) : refl _
|
||
... = concat (concat (reverse t) (reverse l)) (cons x nil) : { H }
|
||
... = concat (reverse t) (concat (reverse l) (cons x nil)) : concat_assoc _ _ _
|
||
... = concat (reverse t) (reverse (cons x l)) : refl _)
|
||
|
||
theorem reverse_reverse (l : list T) : reverse (reverse l) = l :=
|
||
list_induction_on l (refl _)
|
||
(take x l',
|
||
assume H: reverse (reverse l') = l',
|
||
show reverse (reverse (cons x l')) = cons x l', from
|
||
calc
|
||
reverse (reverse (cons x l')) =
|
||
concat (reverse (cons x nil)) (reverse (reverse l')) : {reverse_concat _ _}
|
||
... = cons x l' : {H})
|
||
|
||
-- longer versions:
|
||
|
||
-- reverse (reverse (cons x l)) =
|
||
-- concat (reverse (cons x nil)) (reverse (reverse l)) : {reverse_concat _ _}
|
||
-- ... = concat (reverse (cons x nil)) l : {H}
|
||
-- ... = cons x l : refl _)
|
||
|
||
-- calc
|
||
-- reverse (reverse (cons x l)) = reverse (concat (reverse l) (cons x nil))
|
||
-- : refl _
|
||
-- ... = concat (reverse (cons x nil)) (reverse (reverse l)) : {reverse_concat _ _}
|
||
-- ... = concat (reverse (cons x nil)) l : {H}
|
||
-- ... = cons x l : refl _)
|
||
|
||
-- before:
|
||
-- calc
|
||
-- reverse (reverse (cons x l)) = reverse (concat (reverse l) (cons x nil))
|
||
-- : {reverse_cons x l}
|
||
-- ... = concat (reverse (cons x nil)) (reverse (reverse l)) : {reverse_concat _ _}
|
||
-- ... = concat (reverse (cons x nil)) l : {H}
|
||
-- ... = concat (concat (reverse nil) (cons x nil)) l : {reverse_cons _ _}
|
||
-- ... = concat (concat nil (cons x nil)) l : {reverse_nil}
|
||
-- ... = concat (cons x nil) l : {nil_concat _}
|
||
-- ... = cons x (concat nil l) : cons_concat _ _ _
|
||
-- ... = cons x l : {nil_concat _})
|
||
|
||
|
||
-- Append
|
||
-- ------
|
||
|
||
-- TODO: define reverse from append
|
||
|
||
definition append (x : T) : list T → list T := list_rec (x :: nil) (fun y l l', y :: l')
|
||
|
||
theorem append_nil (x : T) : append x nil = [x] := refl _
|
||
|
||
theorem append_cons (x : T) (y : T) (l : list T) : append x (y :: l) = y :: (append x l) := refl _
|
||
|
||
theorem append_eq_concat (x : T) (l : list T) : append x l = l ++ [x] :=
|
||
list_induction_on l (refl _)
|
||
(take y l,
|
||
assume P : append x l = concat l [x],
|
||
P ▸ refl _)
|
||
|
||
-- calc
|
||
-- append x (cons y l) = concat (cons y l) (cons x nil) : { P })
|
||
|
||
-- calc
|
||
-- append x (cons y l) = cons y (concat l (cons x nil)) : { P }
|
||
-- ... = concat (cons y l) (cons x nil) : refl _)
|
||
|
||
-- here it works!
|
||
-- append x (cons y l) = cons y (append x l) : refl _
|
||
-- ... = cons y (concat l (cons x nil)) : { P }
|
||
-- ... = concat (cons y l) (cons x nil) : refl _)
|
||
|
||
theorem append_eq_reverse_cons (x : T) (l : list T) : append x l = reverse (x :: reverse l) :=
|
||
list_induction_on l
|
||
(calc
|
||
append x nil = [x] : (refl _)
|
||
... = concat nil [x] : {symm (nil_concat _)}
|
||
... = concat (reverse nil) [x] : {symm (reverse_nil)}
|
||
... = reverse [x] : {symm (reverse_cons _ _)}
|
||
... = reverse (x :: (reverse nil)) : {symm (reverse_nil)})
|
||
(take y l',
|
||
assume H : append x l' = reverse (x :: reverse l'),
|
||
calc
|
||
append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat _ _
|
||
... = concat (reverse (reverse (y :: l'))) [ x ] : {symm (reverse_reverse _)}
|
||
... = reverse (x :: (reverse (y :: l'))) : refl _)
|
||
|
||
|
||
-- Head and tail
|
||
-- -------------
|
||
|
||
definition head (x0 : T) : list T → T := list_rec x0 (fun x l h, x)
|
||
|
||
theorem head_nil (x0 : T) : head x0 (@nil T) = x0 := refl _
|
||
|
||
theorem head_cons (x : T) (x0 : T) (t : list T) : head x0 (x :: t) = x := refl _
|
||
|
||
theorem head_concat (s t : list T) (x0 : T) : s ≠ nil → (head x0 (s ++ t) = head x0 s) :=
|
||
list_cases_on s
|
||
(take H : nil ≠ nil, absurd_elim (head x0 (concat nil t) = head x0 nil) (refl nil) H)
|
||
(take x s,
|
||
take H : cons x s ≠ nil,
|
||
calc
|
||
head x0 (concat (cons x s) t) = head x0 (cons x (concat s t)) : {cons_concat _ _ _}
|
||
... = x : {head_cons _ _ _}
|
||
... = head x0 (cons x s) : {symm ( head_cons x x0 s)})
|
||
|
||
definition tail : list T → list T := list_rec nil (fun x l b, l)
|
||
|
||
theorem tail_nil : tail (@nil T) = nil := refl _
|
||
|
||
theorem tail_cons (x : T) (l : list T) : tail (cons x l) = l := refl _
|
||
|
||
theorem cons_head_tail (x0 : T) (l : list T) : l ≠ nil → (head x0 l) :: (tail l) = l :=
|
||
list_cases_on l
|
||
(assume H : nil ≠ nil, absurd_elim _ (refl _) H)
|
||
(take x l, assume H : cons x l ≠ nil, refl _)
|
||
|
||
|
||
-- List membership
|
||
-- ---------------
|
||
|
||
definition mem (f : T) : list T → Prop := list_rec false (fun x l H, (H ∨ (x = f)))
|
||
|
||
infix `∈` : 50 := mem
|
||
|
||
theorem mem_nil (f : T) : mem f nil ↔ false := iff_refl _
|
||
|
||
theorem mem_cons (x : T) (f : T) (l : list T) : mem f (cons x l) ↔ (mem f l ∨ x = f) := iff_refl _
|
||
|
||
-- TODO: fix this!
|
||
-- theorem or_right_comm : ∀a b c, (a ∨ b) ∨ c ↔ (a ∨ c) ∨ b :=
|
||
-- take a b c, calc
|
||
-- (a ∨ b) ∨ c ↔ a ∨ (b ∨ c) : or_assoc _ _ _
|
||
-- ... ↔ a ∨ (c ∨ b) : {or_comm _ _}
|
||
-- ... ↔ (a ∨ c) ∨ b : (or_assoc _ _ _)⁻¹
|
||
|
||
-- theorem mem_concat_imp_or (f : T) (s t : list T) : mem f (concat s t) → mem f s ∨ mem f t :=
|
||
-- list_induction_on s
|
||
-- (assume H : mem f (concat nil t),
|
||
-- have H1 : mem f t, from subst H (nil_concat t),
|
||
-- show mem f nil ∨ mem f t, from or_intro_right _ H1)
|
||
-- (take x l,
|
||
-- assume IH : mem f (concat l t) → mem f l ∨ mem f t,
|
||
-- assume H : mem f (concat (cons x l) t),
|
||
-- have H1 : mem f (cons x (concat l t)), from subst H (cons_concat _ _ _),
|
||
-- have H2 : mem f (concat l t) ∨ x = f, from (mem_cons _ _ _) ◂ H1,
|
||
-- have H3 : (mem f l ∨ mem f t) ∨ x = f, from imp_or_left H2 IH,
|
||
-- have H4 : (mem f l ∨ x = f) ∨ mem f t, from or_right_comm _ _ _ ◂ H3,
|
||
-- show mem f (cons x l) ∨ mem f t, from subst H4 (symm (mem_cons _ _ _)))
|
||
|
||
-- theorem mem_or_imp_concat (f : T) (s t : list T) :
|
||
-- mem f s ∨ mem f t → mem f (concat s t)
|
||
-- :=
|
||
-- list_induction_on s
|
||
-- (assume H : mem f nil ∨ mem f t,
|
||
-- have H1 : false ∨ mem f t, from subst H (mem_nil f),
|
||
-- have H2 : mem f t, from subst H1 (or_false_right _),
|
||
-- show mem f (concat nil t), from subst H2 (symm (nil_concat _)))
|
||
-- (take x l,
|
||
-- assume IH : mem f l ∨ mem f t → mem f (concat l t),
|
||
-- assume H : (mem f (cons x l)) ∨ (mem f t),
|
||
-- have H1 : ((mem f l) ∨ (x = f)) ∨ (mem f t), from subst H (mem_cons _ _ _),
|
||
-- have H2 : (mem f t) ∨ ((mem f l) ∨ (x = f)), from subst H1 (or_comm _ _),
|
||
-- have H3 : ((mem f t) ∨ (mem f l)) ∨ (x = f), from subst H2 (symm (or_assoc _ _ _)),
|
||
-- have H4 : ((mem f l) ∨ (mem f t)) ∨ (x = f), from subst H3 (or_comm _ _),
|
||
-- have H5 : (mem f (concat l t)) ∨ (x = f), from (or_imp_or_left H4 IH),
|
||
-- have H6 : (mem f (cons x (concat l t))), from subst H5 (symm (mem_cons _ _ _)),
|
||
-- show (mem f (concat (cons x l) t)), from subst H6 (symm (cons_concat _ _ _)))
|
||
|
||
-- theorem mem_concat (f : T) (s t : list T) : mem f (concat s t) ↔ mem f s ∨ mem f t
|
||
-- := iff_intro (mem_concat_imp_or _ _ _) (mem_or_imp_concat _ _ _)
|
||
|
||
-- theorem mem_split (f : T) (s : list T) :
|
||
-- mem f s → ∃ a b : list T, s = concat a (cons f b)
|
||
-- :=
|
||
-- list_induction_on s
|
||
-- (assume H : mem f nil,
|
||
-- have H1 : mem f nil ↔ false, from (mem_nil f),
|
||
-- show ∃ a b : list T, nil = concat a (cons f b), from absurd_elim _ H (eqf_elim H1))
|
||
-- (take x l,
|
||
-- assume P1 : mem f l → ∃ a b : list T, l = concat a (cons f b),
|
||
-- assume P2 : mem f (cons x l),
|
||
-- have P3 : mem f l ∨ x = f, from subst P2 (mem_cons _ _ _),
|
||
-- show ∃ a b : list T, cons x l = concat a (cons f b), from
|
||
-- or_elim P3
|
||
-- (assume Q1 : mem f l,
|
||
-- obtain (a : list T) (PQ : ∃ b, l = concat a (cons f b)), from P1 Q1,
|
||
-- obtain (b : list T) (RS : l = concat a (cons f b)), from PQ,
|
||
-- exists_intro (cons x a)
|
||
-- (exists_intro b
|
||
-- (calc
|
||
-- cons x l = cons x (concat a (cons f b)) : { RS }
|
||
-- ... = concat (cons x a) (cons f b) : (symm (cons_concat _ _ _)))))
|
||
-- (assume Q2 : x = f,
|
||
-- exists_intro nil
|
||
-- (exists_intro l
|
||
-- (calc
|
||
-- cons x l = concat nil (cons x l) : (symm (nil_concat _))
|
||
-- ... = concat nil (cons f l) : {Q2}))))
|
||
|
||
-- -- Find
|
||
-- -- ----
|
||
|
||
-- definition find (x : T) : list T → ℕ
|
||
-- := list_rec 0 (fun y l b, if x = y then 0 else succ b)
|
||
|
||
-- theorem find_nil (f : T) : find f nil = 0
|
||
-- :=refl _
|
||
|
||
-- theorem find_cons (x y : T) (l : list T) : find x (cons y l) =
|
||
-- if x = y then 0 else succ (find x l)
|
||
-- := refl _
|
||
|
||
-- theorem not_mem_find (l : list T) (x : T) : ¬ mem x l → find x l = length l
|
||
-- :=
|
||
-- @list_induction_on T (λl, ¬ mem x l → find x l = length l) l
|
||
-- -- list_induction_on l
|
||
-- (assume P1 : ¬ mem x nil,
|
||
-- show find x nil = length nil, from
|
||
-- calc
|
||
-- find x nil = 0 : find_nil _
|
||
-- ... = length nil : by simp)
|
||
-- (take y l,
|
||
-- assume IH : ¬ (mem x l) → find x l = length l,
|
||
-- assume P1 : ¬ (mem x (cons y l)),
|
||
-- have P2 : ¬ (mem x l ∨ (y = x)), from subst P1 (mem_cons _ _ _),
|
||
-- have P3 : ¬ (mem x l) ∧ (y ≠ x),from subst P2 (not_or _ _),
|
||
-- have P4 : x ≠ y, from ne_symm (and_elim_right P3),
|
||
-- calc
|
||
-- find x (cons y l) = succ (find x l) :
|
||
-- trans (find_cons _ _ _) (not_imp_if_eq P4 _ _)
|
||
-- ... = succ (length l) : {IH (and_elim_left P3)}
|
||
-- ... = length (cons y l) : symm (length_cons _ _))
|
||
|
||
-- -- nth element
|
||
-- -- -----------
|
||
|
||
-- definition nth (x0 : T) (l : list T) (n : ℕ) : T
|
||
-- := nat.rec (λl, head x0 l) (λm f l, f (tail l)) n l
|
||
|
||
-- theorem nth (x0 : T) (l : list T) : nth_element x0 l 0 = head x0 l
|
||
-- := hcongr1 (nat::rec_zero _ _) l
|
||
|
||
-- theorem nth_element_succ (x0 : T) (l : list T) (n : ℕ) :
|
||
-- nth_element x0 l (succ n) = nth_element x0 (tail l) n
|
||
-- := hcongr1 (nat::rec_succ _ _ _) l
|
||
|
||
-- end
|